O papel da imprensa no movimento da matemática moderna - Nakashima, Mario Nobuyuki (2007)
The present work analyzes the treatment given by the press to the Modern Mathematics Movement in Brazil (MMM), especially in São Paulo State, headquarters of the MMM. We had searched on journalistic texts, of 1960-1980, answers for our main research question: which was the role of the press in the MMM? The research sources had been obtained from archives of newspapers named Folha de São Paulo and State of São Paulo. To these newspapers archives were added up newspaper clippings from APOS Osvaldo Sangiorgi s Personal Archive, donated by professor Osvaldo Sangiorgi to the Research Group of the History of Mathematics Education GHEMAT, from Pontifícia Universidade Católica de São Paulo PUC-SP. Firstly, this research had analyzed the academic works about MMM, verifying as these studies had used newspapers articles as research source. Secondly, we had taken as basis the studies of the historian Jacques Le Goff, which had supplied excellent elements to analyze the journalistic texts under the document/monument perspective. We considered, still, Christopher Prochasson s studies, which discuss the interest for private archives along the History of historiographical practices. We also considered the studies of the journalist Florence Aubenas and the studies of the philosopher Miguel Benasayag, because both theorized on the role of the mass media in society. We concluded that there are some factors that justify the support of newspapers in the spreading of MMM, as follows: the close relationship between MMM protagonists and government leaders; the friendship between journalists and MMM divulgers; the valuation given to Mathematics Education in order to reduce dictatorship authoritarianism; and the previous censorship to social and political texts allied to the political impartiality of Mathematics. At the same time, MMM protagonists had used to advantage this spreading to propagate MMM ideology in society